Promoting Glucose Transporter-4 Vesicle Trafficking along Cytoskeletal Tracks: PAK-Ing Them Out - Tunduguru, Ragadeepthi; Thurmond, Debbie C. (Frontiers in Endocrinology, 2017)
Glucose is the principal cellular energy source in humans and maintenance of glucose homeostasis is critical for survival. Glucose uptake into peripheral skeletal muscle and adipose tissues requires the trafficking of vesicles containing glucose transporter-4 (GLUT4) from the intracellular storage compartments to the cell surface. Trafficking of GLUT4 storage vesicles (GSVs) is initiated via the canonical insulin signaling cascade in skeletal muscle and fat cells, as well as via exercise-induced contraction in muscle cells. Recent studies have elucidated steps in the signaling cascades that involve remodeling of the cytoskeleton, a process that underpins the mechanical movement of GLUT4 vesicles. This review is focused upon an alternate PI-3 kinase-dependent pathway involving Rac1 signaling through the p21-activated kinase PAK1 and showcases related signaling events that co-regulate both the depolymerization and re-polymerization of filamentous actin (F-actin). These new insights provide an enriched understanding into the process of glucose transport and yield potential new targets for interventions aimed to improve insulin sensitivity and remediate insulin resistance, pre-diabetes and the progression to type 2 diabetes.